Changes in treatment for NSTEMI in women and the elderly over the past 16 years in a large real-world population. (1st October 2020) - Riehle, Leonhard; Maier, Birga; Behrens, Steffen; Bruch, Leonhard; Schoeller, Ralph; Schühlen, Helmut; Stockburger, Martin; Theres, Heinz; Leistner, David M.; Landmesser, Ulf; Fröhlich, Georg M.
Abstract: Aims: This study investigates the changes in therapy for Non-ST-Elevation Myocardial Infarction (NSTEMI) over the past 16 years in a large German registry. In particular, the high-risk population of female and elderly patients was analyzed. Methods: In total, 19.383 patients presenting with NSTEMI were included in this study. Patients were stratified by age groups <75 years and ≥75 years and by sex. Four different time periods from 2000–2004, 2005–2008, 2009–2012 and 2013–2016 were compared. Influence on hospital mortality as the primary outcome measure was assessed by logistic regression analysis. Secondary outcome measures included percutaneous coronary intervention (PCI), the use of drug eluting stents (DES), radial access route and major adverse cardiovascular events (MACE), defined as all-cause mortality, stroke, re-infarction, percutaneous re-intervention, intervention-related bleeding, cardiopulmonary resuscitation and new onset of cardiogenic shock or need for mechanical ventilation. Results: Mortality decreased in all age groups between the initial time period and the most recent one (8.9% vs. 4.5%, p < 0.01), particularly in female patients ≥75 years (18.2% in 2000–2004 vs. 7.9% in 2013–2016, p < 0.01). Revascularization rates differed by gender (68.3% in women vs. 78.1% in men, p < 0.01) and by age (64.2% for ≥75 years vs. 80.9% for <75 years, p < 0.01). PCI rates in elderly female patients increased from 28.7% to 69.8% (p < 0.01) from the initial to the latest period. Conclusions: The present study demonstrates, that revascularization rates improved in all patient groups over the study period. However, females and elderly patients still remain less likely to be treated according to current guidelines. Highlights: The study demonstrates an increase in revascularization rates in patients with NSTEMI in all different subsets of patients Females and elderly patients remain less likely to be treated according to current guidelines In elderly patients ≥75 years, female sex remains and independent risk factor for in-hospital mortality There is still more effort to be made to reduce delays in hospital admission in female and elderly patient